Intensity Correction and Pole Figure Measurement of Copper Metallic by XRD - Halo Dalshad Omar (Journal of Basic & Applied Sciences, 2016)
In this research work the process of data intensity correction and pole figure measurement were investigated and analyzed by using X-Ray Diffraction (XRD) technique. Different corrections were studied, to see their influence on the crystallographic texture analysis. Specific software, which is Labotex was used to determine the pole figure for copper (Cu) metallic after which the data corrections have been made. The copper, Cu sample was simply prepared by a low cost method Mini Mill 2 Panalytical and the sample was rotated for 10 minutes by grinding the sample at high speed of 250 rpm.